(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Responding to the current development of information and communication technology is very rapid, as evidenced by the contrast in people’s dependence on the internet. One example is the current economic sector, which is marked by the growth of an online-based buying and selling system usually called an online business. This study aims to reconstruct a technology-based financing scheme by utilizing FinTech as a platform based on mudharabah contracts. The sample used in this study was three people consisting of IAIN Fattahul Muluk Papuan students and Wirauaha Gen Z in Jayapura. The method used in this research is a qualitative approach method. The results of the study show that in doing business online, there are obstacles faced by business people, namely, minimal capital, difficulty getting an agent as a business partner, difficulty getting a trusted agent, and difficulty communicating with agents.